Pengaruh kecerdasan intelektual dan kecerdasan emosional terhadap prestasi belajar fiqih siswa di MIM Randulas Pulutan Nogosari - Nashihun Nashihun; Mujiburrohman Mujiburrohman; Joko Subando (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
The purpose of this study was: to determine the effect of intellectual intelligence and emotional intelligence on students' achievement in learning jurisprudence at MIM Randulas Pulutan Nogosari. This type of research is to use a quantitative research approach and use primary data. The population in this study were 30 grade 4 students of MIM Randulas Pulutan Nogosari. Test analysis in this study using multiple linear regression test, t-test, F test, and the value of the coefficient of determination (R2). Based on the results of this study it can be concluded that: 1) intellectual intelligence has a significant effect on the learning achievement of fiqh students of MIM Randulas Pulutan Nogosari. 2) emotional intelligence has a significant effect on the learning achievement of fiqh students of MIM Randulas Pulutan Nogosari.